2020
DOI: 10.4081/bollettinosei.2020.75
|View full text |Cite
|
Sign up to set email alerts
|

First report of <em>Baryscapus silvestrii</em> in Calabria, Italy (Chalcidoidea Eulophidae)

Abstract: The eulophid Baryscapus silvestrii Viggiani & Bernardo is reported for the first time in the Calabria region (Southern Italy). Adults of the eulophid emerged in September 2019 from olive fruit fly Bactrocera oleae (Diptera Tephritidae) puparia detected during a survey in an experimental olive groove in Mirto Crosia in Cosenza province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Specifically, three ectoparasitoids ( Figure 5 ): Eurytoma martellii Domenichini (Hymenoptera: Chalcidoidea, Eurytomidae) , Prolasioptera berlesiana Paoli (Diptera: Cecidomyiidae) and Eupelmus urozonus Dalman (Hymenoptera: Chalcidoidea, Eupelmidae), and two endoparasitoids ( Figure 6 ): Psyttalia concolor Szépligeti (Hymenoptera: Braconidae) , and Baryscapus sylvestrii Viggiani& Bernardo (Hymenoptera: Chalcidoidea, Eulophidae), were identified. As regards the latter, it was during this trial that this insect was first observed in Calabria [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, three ectoparasitoids ( Figure 5 ): Eurytoma martellii Domenichini (Hymenoptera: Chalcidoidea, Eurytomidae) , Prolasioptera berlesiana Paoli (Diptera: Cecidomyiidae) and Eupelmus urozonus Dalman (Hymenoptera: Chalcidoidea, Eupelmidae), and two endoparasitoids ( Figure 6 ): Psyttalia concolor Szépligeti (Hymenoptera: Braconidae) , and Baryscapus sylvestrii Viggiani& Bernardo (Hymenoptera: Chalcidoidea, Eulophidae), were identified. As regards the latter, it was during this trial that this insect was first observed in Calabria [ 48 ].…”
Section: Resultsmentioning
confidence: 99%